If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -1(25x + -18) = 34x + -1(15x + -30) + 18 Reorder the terms: 14x + -1(-18 + 25x) = 34x + -1(15x + -30) + 18 14x + (-18 * -1 + 25x * -1) = 34x + -1(15x + -30) + 18 14x + (18 + -25x) = 34x + -1(15x + -30) + 18 Reorder the terms: 18 + 14x + -25x = 34x + -1(15x + -30) + 18 Combine like terms: 14x + -25x = -11x 18 + -11x = 34x + -1(15x + -30) + 18 Reorder the terms: 18 + -11x = 34x + -1(-30 + 15x) + 18 18 + -11x = 34x + (-30 * -1 + 15x * -1) + 18 18 + -11x = 34x + (30 + -15x) + 18 Reorder the terms: 18 + -11x = 30 + 18 + 34x + -15x Combine like terms: 30 + 18 = 48 18 + -11x = 48 + 34x + -15x Combine like terms: 34x + -15x = 19x 18 + -11x = 48 + 19x Solving 18 + -11x = 48 + 19x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19x' to each side of the equation. 18 + -11x + -19x = 48 + 19x + -19x Combine like terms: -11x + -19x = -30x 18 + -30x = 48 + 19x + -19x Combine like terms: 19x + -19x = 0 18 + -30x = 48 + 0 18 + -30x = 48 Add '-18' to each side of the equation. 18 + -18 + -30x = 48 + -18 Combine like terms: 18 + -18 = 0 0 + -30x = 48 + -18 -30x = 48 + -18 Combine like terms: 48 + -18 = 30 -30x = 30 Divide each side by '-30'. x = -1 Simplifying x = -1
| 4r+2(r-2)= | | 5(6+2)= | | w^3-6w^2-27w= | | y=20x-2x^2-50 | | 5-3x=3(4-2x) | | -5=-4(x-1) | | 8s=21 | | -2(x+4)=5 | | 2=-2+24 | | 7(4+x)=20 | | 6+8x=-7+x | | 5=-2x-27 | | f(x)=2x^2-12x+15 | | 28-5x=13-10x | | x/2-x/5=9/10 | | 15-(9+10b)+(20b-4)=22 | | 5q=4+3p | | p^2+8p-5=0 | | y=37320-50x | | 3x^2-5x+k=0 | | 1/x-1/y=11 | | 24=60-4Q | | 11-3n=19 | | 2x-2=4222 | | 2x-2=422 | | 2x-2=42 | | 4x-18=5x+2 | | (x-2)+2(2x+5)=3(2x+5) | | 1x*1x-3x=0 | | a*x+b*y=c*z | | 5x-5*(2/15)*-4 | | p=15-5q/4 |